Chicken soup for the soul teens talk growing up : stories about growing up, meeting challenges, and learning from life - Canfield, Jack 1944-; Hanson, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Pub., 2008)
Collects anecdotes from teenagers about friendship, peer pressure, self-acceptance, family life, relationships, and overcoming obstacles.